Competition for Natural Resources and the Hold-Up Problem - Carsten Hefeker; Sebastian Kessing (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the role of competition for the hold-up problem in foreign direct investment in resource-based industries. The host country government is not only unable to commit not to expropriate investment ex post, but is also unable to commit to the provision of local resources. In the case of competition for local resources this dual commitment problem triggers higher investment levels and increases host country revenues, but hurts pro.ts of international investors.
Keywords: F21; F23; Q34; 330; foreign direct investment; natural resources; hold-up problem